Career Crafting Strategies Developed by Generation Z in Navigating Career Uncertainty: A Multi-Case Study in the Creative Sector: Generation Z faces an existential paradox: - Erma Wijayanti; Ruswiati Surya Saputra; Muliati (Journal of Economics and Management, 2026)
Career uncertainty has become a structural condition confronting Generation Z within Indonesia's creative sector, marked by high layoff rates, global competition, and technological disruption. Unlike job crafting approaches that focus on modifying tasks within an organization, this study introduces career crafting as a more fundamental process of career construction beyond organizational boundaries. Employing a qualitative approach with a multi-case study design, this research involved 24 Generation Z participants aged 18–27 working as content creators, freelance designers, creative startup founders, and portfolio workers in Jakarta, Bandung, and Yogyakarta. Data were collected through semi-structured interviews, digital observations, and documentation, and analyzed using reflexive thematic analysis. The findings identify three primary career-crafting strategies: portfolio polymorphism through cross-platform diversification and algorithmic management; communal buffering through the formation of collectives as a mechanism for collective risk mitigation; and existential pivoting, characterized by a shift in values from passion toward well-being as a career orientation. This study extends Career Construction Theory by demonstrating that Generation Z's career adaptability is realized through proactive withdrawal rather than merely adjusting to existing structures. Policy implications highlight the need for portable social protection schemes and community-based creative infrastructure.